Theoretical Analysis and Systematic Deconstruction of High Quality Development of Public Service for National Fitness - Deng, Liang (Quality in Sport, 2025)
This study conducts a theoretical and systematic analysis of high-quality development (HQD) in China’s National Fitness Public Service (NFPS). By integrating the principles of HQD—such as innovation, coordination, green development, openness, and sharing—with the practical demands of NFPS, we propose a multi-dimensional governance framework that emphasizes dynamic adaptation between service supply and public demand. Through literature review, case studies (e.g., Shandong Province), and comparative analysis (e.g., England’s urban-rural disparity), we identify key challenges including fragmented governance, resource imbalance, and inadequate technological integration. A "process-result" analytical model is developed to highlight the roles of digital empowerment (e.g., blockchain, big data platforms) and performance evaluation mechanisms in optimizing service equity and sustainability. The findings underscore the necessity of collaborative governance among government, market, and society, while advocating for policy innovations to address regional disparities. This research not only enriches the theoretical discourse on public health governance but also offers actionable insights for global contexts striving to achieve inclusive fitness service systems.